A Framework for Risk-Energy Aware Service-Level Agreement Provisioning (RESP) for Computing the Quickest Path. (6th May 2019) - Sharma, Ashutosh; Kumar, Rajiv
Abstract : This paper involved the computation of quickest paths with the help of service-level agreement (SLA) and energy constraints. The consideration of these constraints helps to propose a novel system model which computes the path to strengthen the continuity and criticality of the data transmission. The proposed risk-energy aware SLA provisioning (RESP) system model incorporates the research gaps of the existing risk assessment models in the literature without any increase in time complexity. The formulation of RESP shows the usefulness in the critical applications. The results show that the computation of risk-provisioned path gives the SLA satisfied paths and has a great impact of variations in the data traffic. The performance of the proposed algorithm has been indicated in terms of different performance parameters such as means − t paths, average hop counts, and average energy efficiency. Simulation result implies that as data traffic increases, the number of the risk‐provisioneds − t paths decreases whereas corresponding average hop counts and average energy efficiency increases.